Pencegahan Anemia Untuk Menurunkan Angka Stunting Berbasis Aplikasi Android Fikes-BlesD di SMA Dr. Soetomo Surabaya - Arkha Rosyaria Badrus; Nurul Fathiyyah; Kholifatul Ummah; Alief Ayu Purwitasari (Health Care : Journal of Community Service, 2026)
Low reproductive health literacy and a high risk of anemia among adolescents demand sustainable educational interventions. The partner (SMA Dr. Soetomo) has implemented regular health checks and anemia screening; however, these activities are time-limited, do not yet allow for independent screening, and lack digital media support for control and monitoring by the school or health workers. The educational application "Fikes-BleSD" was developed as a digital solution to address these limitations. The objective of this community service (PKM) is to evaluate the effectiveness of Fikes-BleSD empowerment in increasing reproductive health knowledge, compliance with Blood-Added Tablet (TTD) consumption, and hemoglobin (Hb) indicators, as well as strengthening school-based monitoring mechanisms. The method used is a participatory approach including multimedia content development, training for teachers and peer educators, the launch of the application featuring reminders and monitoring dashboards, as well as quantitative pre-post evaluations (knowledge questionnaires, TTD compliance) and Hb screening. The results found that >90% of female students downloaded the application; ≥80% activated TTD reminders; knowledge scores increased significantly (≥30%); compliance and dietary patterns improved; and an increase in Hb was observed in the compliant group. Integration into the School Health Unit (UKS) and the formation of a digital team ensure sustainability. The conclusion of this PKM is that Fikes-BleSD effectively overcomes the limitations of periodic control activities by providing a means for independent screening and digital monitoring, making it feasible for replication in other schools.